Correlates of sex trading among male non-injecting drug users in Myanmar: a cross-sectional study. Issue 1 (December 2016) - Saw, Yu; Saw, Thu; Wai, Kyi; Poudel, Krishna; Win, Hla
Abstract Background Sex trading is a recognized risk factor for human immune deficiency virus infection and other sexually transmitted infections among non-injecting drug users (NIDUs). However, very little research has addressed the factors associated with sex trading among male NIDUs in Myanmar. Methods A cross-sectional study was conducted from January to February 2010 using the respondent-driven sampling method. In total, 210 NIDUs aged between 18 and 49 years, with no history of injecting drug use, and who used non-injected illicit drugs in the last 6 months were recruited. Face-to-face interviews were conducted using a structured questionnaire to collect information on participants' sexual and drug use behaviors. Binary and multivariate logistic regressions were applied to analyze the resulting data. Results Of 210 NIDUs, 84 (40%) reported involvement in the sex trade during the last 3 months. In the adjusted model, factors associated with sex trade involvement included homosexual preference (adjusted odds ratio [AOR] 4.90; 95% confidence interval [CI] 1.61–14.95), having more than two partners (AOR = 3.88; 95% CI 1.55–9.72), had a regular job (AOR = 5.10; 95% CI 1.65–15.72), use of stimulant drugs rather than opiate (AOR = 2.38; 95% CI 1.10–5.15), and who used drugs more than twice per day. Conclusions More than one third of NIDUs were involved in sex trading. This study suggested that further comprehensive intervention programs that aim to reduce risk factors of trading sex among NIDUs may consider including NIDUs who used stimulant drugs, had regular/full-time jobs, used drugs more than twice per day, and had homosexual preferences.